2005
DOI: 10.1086/432636
|View full text |Cite
|
Sign up to set email alerts
|

ChandraStudy of X‐Ray Point Sources in the Early‐Type Galaxy NGC 4552 (M89)

Abstract: We present a Chandra ACIS study of the early-type galaxy NGC 4552. We detect 47 X-ray point sources, most of which are likely low mass X-ray binaries (LMXBs), within 4 effective radii (R e ). The brightest X-ray source coincides with the optical, UV and radio center of the galaxy, and shows variability on > 1 hr timescales, indicating the possible existence of a low-luminosity AGN. The 46 offcenter sources and the unresolved point sources contribute about 29% and 20% to the total luminosity of the galaxy, resp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 41 publications
5
29
4
Order By: Relevance
“…The GregoryLoredo analysis failed to find any statistically significant evidence for variability on shorter timescales, i.e., in the m > 2 moments. Thus, we find no statistical evidence in these data to support the claim by Xu et al (2005) that was based on their ''visual inspection of the light curve,'' for X-ray variability on 1 hr timescales.…”
Section: The Nuclear Regioncontrasting
confidence: 95%
“…The GregoryLoredo analysis failed to find any statistically significant evidence for variability on shorter timescales, i.e., in the m > 2 moments. Thus, we find no statistical evidence in these data to support the claim by Xu et al (2005) that was based on their ''visual inspection of the light curve,'' for X-ray variability on 1 hr timescales.…”
Section: The Nuclear Regioncontrasting
confidence: 95%
“…Both sources in NGC 4472, (+12:29:42.33, +08:00:07.96) and (+12:29:41.00, +07:57:44.46) were previously reported by Maccarone et al (2003Maccarone et al ( , 2011, respectively. Of the two sources in NGC 4552, one (+12:35:45.77, +12:33:02.46) was previously known (Xu et al 2005), while the other (+12:35:41.22, +12:34:51.43) is, to our knowledge, a new identification.…”
Section: Nature Of (Ultra-) Luminous X-ray Sourcesmentioning
confidence: 66%
“…However, three of the Chandra observations are not public yet, so the only reported results came from Chandra Obs ID 2072 (Filho et al 2004;Xu et al 2005;González-Martín et al 2009b;Grier et al 2011;Boroson et al 2011). Filho et al (2004 and González-Martín et al (2009b) In the UV, Cappellari et al (1999) studied this LINER with both HST imaging (FOC) and spectroscopy (FOS), with images taken in 1991, 1993, and 1996, showing long-term variability. This agrees with Maoz et al (2005), who used HST-ACS observations with its HRC mode and found a 20% variation of the nuclear flux in both F250W and F330W bands.…”
Section: Appendix A: Notes and Comparisons With Previous Results For mentioning
confidence: 99%